Implementasi Sistem Pengendalian Internal dalam Tata Kelola Keuangan Minimarket : Kajian Praktis Berbasis Program Pengabdian Masyarakat - Siska Yulia Defitri; Dillfa Lailatul Rahmi Dani; Alifa Deisma Rizika; Iis Daryanti; Sarah Sarah; Witra Maison; Nidia Anggreni Das (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
This community service initiative aims to educate and assist in the implementation of an Internal Control System ICS at Minimarket Malika as a strategic effort to safeguard assets and enhance operational effectiveness and efficiency. The ICS applied includes a systematic recording process for inventory, purchase prices, and selling prices. These records are intended to ensure that all transactions are properly documented and accountable.Internal evaluations are conducted regularly through annual stock-taking activities, which involve verifying and matching inventory data recorded in the system with the actual physical stock in the store or warehouse. This activity serves as a critical benchmark for assessing business stability, the accuracy of inventory records, and the overall effectiveness of inventory management. Any transactional errors identified during sales operations are corrected immediately in real-time to prevent error accumulation and potential financial losses. The role of management is essential, particularly in maintaining business continuity through improved service quality and the timely fulfillment of customer needs. In response to intense competition and dynamic market changes, Minimarket Malika adopts adaptive strategies such as price adjustments, excellent customer service, and a broader product assortment to meet diverse consumer demands. To prevent fraud, the minimarket has installed CCTV cameras at strategic locations and provides training for employees on how to detect counterfeit money and suspicious behavior. The ICS also supports risk management in inventory by monitoring the movement of goods in real-time, allowing management to make accurate decisions about which products need to be stocked in accordance with current consumer demand trends.Through the consistent and comprehensive application of an internal control system, Minimarket Malika is expected to improve its competitiveness while maintaining the integrity and sustainability of its business operations amid ongoing economic challenges. Furthermore, this approach serves as a practical model for other small and medium enterprises (SMEs) aiming to strengthen their internal governance and adapt to an increasingly complex retail environment.